(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bombyx mori is domesticated for silk production and is reared in colonial forms. A code of conduct for rearing silkworm is practiced to ensure survival of silkworm and cocooning. One of the major constraints in silk production is the diseases in silkworm rearing.Bacterial infection is well managed by antibiotics, the ability of bacteria to acquire resistance to drugs makes it ineffective within a short duration and hence attempts are being made for the use of plant compounds especially the crude aqueous extracts of plants against silkworm bacterial pathogens. In the present study bacterial pathogens were collected from black thorax Septicemia diseased larvae of silkworm B. mori, the diseased larvae were crushed by using mortar and pestle. As the result the organisms identified were Klebsiella pneumonia, Bacillus subtilis, E.coli and Staphylococcus aureus. The antibacterial activity was assayed by measuring the diameter of the inhibition zone formed around the wells.The zone of inhibition for Staphylococcus aureuswas maximum (12.5±0.7) at 500μg/ml extract concentration. Medicinal plants are cheaper and effective natural antimicrobial agents with better potential, lesser side effects than antibiotics, good bioavailability and minimal toxicity.